2013 American Control Conference 2013
DOI: 10.1109/acc.2013.6580111
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and L<inf>1</inf> adaptive control of pH in bioethanol enzymatic process

Abstract: The enzymatic process is a key step in second generation bioethanol production. Pretreated biomass fibers are liquefied with the help of enzymes to facilitate fermentation. Enzymes are very sensitive to pH and temperature and the main control challenge in the nonlinear process is to ensure minimum deviations from the optimal pH level.This article develops a mathematical model for the pH, which has not been reported earlier for this particular process. The new model embeds flow dynamics and pH calculations and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…xylooligomers, xylose, arabinose, and glucose, react with furfural and 5-HMF to create spherical droplets with a lignin like structure, also known as pseudo-lignin 8 . Furfural and 5-HMF production is important to monitor due to its inhibitory effects on fermentation 7 , while organic acids influence the pH of the enzymatic hydrolysis process 25 . Pseudo-lignin can degrade the enzymatic activity 8 .…”
Section: Mechanistic Modeling For Hydrothermal Mediated Pretreatmentmentioning
confidence: 99%
“…xylooligomers, xylose, arabinose, and glucose, react with furfural and 5-HMF to create spherical droplets with a lignin like structure, also known as pseudo-lignin 8 . Furfural and 5-HMF production is important to monitor due to its inhibitory effects on fermentation 7 , while organic acids influence the pH of the enzymatic hydrolysis process 25 . Pseudo-lignin can degrade the enzymatic activity 8 .…”
Section: Mechanistic Modeling For Hydrothermal Mediated Pretreatmentmentioning
confidence: 99%
“…The numerical search procedure performs various simulations in closed loop, for each simulation evaluating the IAE function from (34). The search algorithm is initialized by following the tuning procedure shown in [14]. A temperature reference of 195 …”
Section: B L 1 Adaptive Controlmentioning
confidence: 99%
“…Since the L 1 -norm is equivalent to an L induced-norm of system input-output signal, it is gained for the stability and the performance assessment of the controller. Several implementations of this controller in various systems such different aircrafts (Hovakimyan and Cao, 2010;Hovakimyan et al, 2011;Capello et al, 2013), missile guidance and control (Erdos et al, 2012), remotely operated vehicles (Maalouf et al, 2013a, b), satellite control (Lee and Singh, 2012b), piezoelectricity actuator (Lee and Singh, 2012a) and control of PH at industrial processes (Prunescu et al, 2013) are successfully reported. Major application of L 1 adaptive controller similar to other adaptive controllers, is in the autonomous vehicles.…”
Section: Introductionmentioning
confidence: 99%